The performance of loan disbursed for micro finance in Bank Simpanan Nasional, Pahang / Faten Aina Mohd Roslim - Mohd Roslim, Faten Aina (Faculty of Business and Management, 2010)
Access of the poor to financial services is indeed important for the success of market based. In this regard, microfinance has been recognized worldwide as an important policy instrument. The attractiveness of microfinance scheme lies in the fact that they provide a mechanism to link micro-entrepreneurs to the much needed credit which are normally inaccessible from the formal financial institutions. Microfinance scheme enable micro-entrepreneurs to expand existing economic activities and consequently in scaling up their income. Currently, there are almost ten financial institution which offers micro finance product and Bank Simpanan Nasional is one of the financial institution which are given a mandate by Bank Negara Malaysia to provide micro finance scheme named BSN Teman Niaga. Since it was introduced by Bank Simpanan Nasional, Pahang, Record of Loan Approved shows that the bank has disbursed for about RM8,253,000 total amount of loan for micro enterprise under manufacturing, service and retail sector. 52 per cent of this amount is disbursed for retail sector, 29 per cent is for service sector and the outstanding balance with total amount of RM1,604,000 is for manufacturing sector. Small and Medium Enterprises (SMEs) in Malaysia contribute to economic development by virtue of their sheer numbers and increasing share in employment and Gross Domestic Product. Their role in the Malaysian economy will strengthen the resilience of the country to face a competitive and challenging global environment.